San Giovanni Maggiore: Architettura e arte alle porte della Napoli antica San Giovanni Maggiore: Architecture and Art at the Gates of Ancient Naples - Raffaele Ruggiero (UrbsHistoriaeImago: Storia e immagine dei territori, dei centri urbani e delle architetture, 2016)
An examination of the literature sources, of the archival documents, of the iconographic and cartographic repertoire to reconstruct the key moments of the fascinating architectural and artistic history of one of the most famous monuments of our city. The Basilica of San Giovanni Maggiore is now the result of often ominous and even criminal events, or of some imprudent interventions, that the recent renovations have been able to remedy only partially. Nevertheless, thanks to the constant care and to the appropriate use by the Engineers Order of Naples, it has been lately given back to the city: not only as an important place of worship, but also as a cultural center and a social gathering site, placed in such a significant area of the historic center of Naples, UNESCO World Heritage since 1995. The architectural and artistic analysis of the Basilica has been preceded by a description of urban history in late Antiquity and in the early Middle Ages; it had its fulcrum in the hill of Monterone, now largo of San Giovanni Maggiore, with an irregular and tortuous web, preserved up to us. This work proposes in the second part an updated summary analysis of existing artistic works in the Basilica, as well as those placed in some other locations in order to be preserved or restored.